DETEKSI PENYAKIT DEMAM BERDARAH MELALUI PERANGKAT LUNAK BERBASIS TEKNOLOGI INFORMASI - agung suryadi; Sri Wahyuningsih Nugraheni (Jurnal Infokes, 2022)
According to the World Health Organitation (WHO), Dengue Hemorrhagic Fever (DHF) around the world has always increased drastically over the last 20 years. DHF is an infectious disease caused by the dengue virus which is transmitted through the bite of the Aedes Aegypti mosquito, characterized by a sudden high fever accompanied by bleeding manifestations and tends to cause shock and death. This disease is one of the most important public health problems in the world in general. The accuracy of decision making from an identification of data in the world of health is very important for patients, because this will affect the patient's treatment services, then this will have an impact on the quality of service in the hospital. This technology has now become a fundamental requirement for the continuity of an organization. By applying information technology to assist clinicians in detecting dengue fever, it will provide convenience and speed in making the diagnosis of dengue fever effectively and efficiently. Based on the information above, the hospital needs a system that can assist clinicians in making a diagnosis. Namely by implementing dengue fever detection software using an information technology-based system. By using a computerized dengue fever detection software that is developed, it will make it easier for a doctor to process and detect patient dengue fever disease data. In addition, with the developed application, it can be easily cooled down that all data will be stored in a database so that a doctor only needs to provide data input according to the needs of the analysis in the application, then the application will provide information in a timely manner so that it will have an impact on improving the quality of service to patients.